2016
DOI: 10.3233/jvr-160817
|View full text |Cite
|
Sign up to set email alerts
|

High-priority employment concerns of Hispanics/Latinos with multiple sclerosis in the United States

Abstract: Abstract. BACKGROUND:Much of previous research on multiple sclerosis (MS) and employment has focused on people of European descent who acquire the disease, and very little is known about the experiences and concerns of people with MS from traditionally underrepresented racial and ethnic groups (e.g., African-Americans, Hispanics/Latinos), even though evidence indicates that the incidence of MS is increasing among non-Caucasians worldwide. OBJECTIVE: The objective of this study was to identify high-priority emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“… 35 Several studies showed that the employment rates were low for non-Caucasian Americans with MS. Hispanics, Afro-Americans, and Afro-American women with MS all had low levels of employment in the US. 35 , 38 , 39 In a recent American study on work loss due to the Covid-19 pandemic, it was found that non-Caucasian persons with MS reported work loss to a higher extent than those identifying as white. 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 Several studies showed that the employment rates were low for non-Caucasian Americans with MS. Hispanics, Afro-Americans, and Afro-American women with MS all had low levels of employment in the US. 35 , 38 , 39 In a recent American study on work loss due to the Covid-19 pandemic, it was found that non-Caucasian persons with MS reported work loss to a higher extent than those identifying as white. 33 …”
Section: Resultsmentioning
confidence: 99%
“…From these studies, it is known that the employment rates for non-Caucasian Americans with MS are low, eg. 38 An American survey study on employment states that African American women with MS are a group that has been given very little attention. 39 Ethnic discrimination in the labor market has been documented among the general population as well.…”
Section: Discussionmentioning
confidence: 99%
“…The PSM procedure utilized in this study en- with an employer, can be a difficult task (Roessler et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of the employment issues facing Hispanics with MS indicate that these individuals have a lower rate of labor force participation and a lower rate of job satisfaction than do Caucasians with MS (Roessler et al, 2016…”
Section: Introductionmentioning
confidence: 99%
“…For instant they had problem with having the accommodation in a short period of time, requesting for assistive technology for their jobs and requesting changes in their tasks without fear of losing their job. [85] is difficult process of requesting accommodation and changing their responsibilities at their job could have a negative impact on keeping their current position. Hence, health professional has an important role in guiding and helping MS patients to remain active at their work.…”
Section: Discussionmentioning
confidence: 99%